Paper Towns - Green, John, 1977- (HarperCollins Publishers, 2013)
Bestseller from the award-winning author of LOOKING FOR ALASKA and THE FAULT IN OUR STARS. Quentin Jacobsen - Q to his friends - is eighteen and has always loved the edgy Margo Roth Spiegelman. As children, they'd discovered a dead body together. Now at high school, Q's nerdy while Margo is uber-cool. One night, Q is basking in the predictable boringness of his life when Margo, dressed as a ninja, persuades him to partake in several hours of mayhem. then she vanishes. While her family shrugs off this latest disappearance, Q follows Margo's string of elaborate clues - including a poem about death. Q's friends Radar, Ben and Lacey help with the search, and a post turns up on a website: Margo will be in a certain location for the next 24 hours only. the race is on! After an epic drive through the night, they catch up with Margo, and Q learns first-hand that the way you think about a person isn't the way they actually are. Ages: 14+.
Imprint: HarperCollins.
Young adult.
Keywords: Bildungsromans; General fiction (Children's / Teenage); Juvenile Fiction - General; Young adult fiction; Missing persons -- Juvenile fiction; Coming of age -- Juvenile fiction; Australian